Controlling the shape and size of BiOBr sheets by varying the bromine source and reactant concentration. (26th May 2021) - Shen, Guodong; Pu, Yongping; Cui, Yongfei; Jing, Panpan; Sun, Runjun
Abstract : BiOBr sheets of tunable shape and size can be obtained by controlling the raw materials and reactant concentration. Abstract : BiOBr sheets of controllable shape and size were synthesized via an ultrasound-assisted co-precipitation method at room temperature by varying the bromine source and reactant concentration. The BiOBr sheets synthesized from KBr and NaBr were rounded rectangles and round, respectively. The size of BiOBr sheets increased with increasing reactant concentration. As the reactant concentration increased from 10 mmol L −1 to 15 mmol L −1 until 20 mmol L −1, the size of as-prepared BiOBr sheets increased from 100–300 nm to 300–500 nm until 700–1000 nm, respectively. Moreover, the size difference in BiOBr sheets did not significantly affect the photocatalytic performance in degrading organic dyes. Such a simple and rapid method of controlling the shape and size of BiOBr sheets could provide more abundant matrix materials for the synthesis and modification of BiOBr.